Μετάφραση από την αγγλική προς την ελληνική γλώσσα και Σχολιασμός αποσπάσματος, από το ερευνητικό άρθρο «Ethiopia and the Tigray War: Limits and Challenges of EU Policy in a Fragmented and Contested Region» των Francesca Caruso και Jesutimilehin O. Akamo - (:unkn) unknown (My University, 2024)
Η παρούσα πτυχιακή εργασία αποτελεί μετάφραση από τα αγγλικά στα ελληνικά και σχολιασμό αποσπάσματος του επιστημονικού άρθρου με τίτλο, «Ethiopia and the Tigray War: Limits and Challenges of EU Policy in a Fragmented and Contested Region», των Francesca Caruso και Jesutimilehin O. Akamo, δημοσιευμένο στο 16ο τεύχος του JOINT, υπό την αιγίδα της Ευρωπαϊκής Ένωσης. Αρχικά, παρουσιάζεται το πρωτότυπο κείμενο στα αγγλικά και έπειτα ακολουθεί το μετάφρασμα. Στη συνέχεια ακολουθεί ο σχολιασμός, ο οποίος αποτελείται από τέσσερα επιμέρους μέρη, την ανάλυση του κειμένου αφετηρίας και της μεταφραστικής εντολής, την αιτιολόγηση λύσεων των προβλημάτων της μετάφρασης και, τέλος, την αξιολόγηση της ποιότητας της μετάφρασης. Τέλος ακολουθεί ένας σύντομος επίλογος και οι βιβλιογραφικές αναφορές.

This thesis is a translation from English into Greek and a commentary of an excerpt of the research article entitled, "Ethiopia and the Tigray War: Limits and Challenges of EU Policy in a Fragmented and Contested Region", by Francesca Caruso and Jesutimilehin O. Akamo, published in the 16th issue of JOINT, under the auspices of the European Union. It starts with the original text in English, followed by the translation. This is followed by the commentary, which consists of four parts, the analysis of the source text and the translation order, the justification of solutions to translation problems and, finally, the evaluation of the quality of the translation. Finally there is a short epilogue and the bibliographical references.
Translation from English to Greek and commentary of an extract from the research article "Ethiopia and the Tigray War: Limits and Challenges of EU Policy in a Fragmented and Contested Region" by Francesca Caruso and Jesutimilehin O. Akamo
Keywords: Αιθιοπία, Κρίση στο Τιγκράι, Γεωπολιτική, Ευρωπαϊκή Ένωση, Εξωτερική Πολιτική, Μετάφραση, Σχολιασμός; Ethiopia, Crisis in Tigray, Geopolitics, European Union, Foreign Policy, Translation, Commentary